Strategy of the National Narcotics Agency of Bengkulu Province in Tackling Drug Abuse Among Adolescents - Muhammad Zefrian; Antonio Imanda; Evi Lorita; Bando Amin C. Kader (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2022)
This study aims to determine the strategy of the National Narcotics Agency of Bengkulu Province in Overcoming Drug Abuse among Teenagers in Bengkulu Province. This research uses qualitative descriptive method, data collections using interviews, observation and documentation. The selection of informants by purposive sampling were six people. Some of the steps that organizations need to take in formulating strategies (Hariadi, 2005), namely: (1) Identifying the environment that the organization will enter in the future and determining the company's mission to achieve the vision. Restricting drugs among teenagers goes according to the vision and mission of the BNNP office to eradicate illicit drug trafficking therefore teenagers and the community are protected from the dangers of drug use. (2) Analyzing the internal and external environment to measure strengths and weaknesses as well as opportunities and threats. There is a lack of support or response from the local government regarding the P4GN program and the lack of uniform socialization conducted by the BNNP Bengkulu Office. (3) Formulating key success factors from the strategies designed based on the previous analysis. The strategy of the BNNP Bengkulu Office has been effective in suppressing the rate of drugs among adolescents. the BNNP Bengkulu Office conducts outreach to schools, campuses and communities by conducting raids among teenagers, providing inspiration and education through social media, TV, radio, cellphones and newspapers. (4) Determining measurable goals and targets, evaluating various alternative strategies by considering the resources owned and the external conditions faced. The employees at the BNNP Bengkulu Office are still lacking in human resources, both in quality and in adequate quantity, and there are limited personnel to control drugs. (5) Choosing the most suitable strategy to achieve short term and long term goals. The BNNP Bengkulu Office already has a short-term socialization and counseling program that is carried out at schools, campuses and the community and in the long-term and the regulations take the form of a regional regulation on P4GN.